2000
DOI: 10.1038/sj.ejhg.5200520
|View full text |Cite
|
Sign up to set email alerts
|

Paternal meiotic origin of der(21;21)(q10;q10) mosaicism [46,XX/46,XX,der(21;21)(q10;q10),+21] in a girl with mild Down syndrome

Abstract: Mosaicism for a derivative 21, der(21;21)(q10;q10), is a rare chromosomal abnormality. Since a normal cell line is present, mitotic origin is considered. Chromosome examination of a female with developmental delay and dysmorphic features compatible with mosaic trisomy 21 revealed a normal cell line and a second cell line with a der(21;21)(q10;q10) [46,XX/46,XX,der(21;21)(q10;q10), + 21]. Molecular investigation with a panel of highly polymorphic microsatellites mapping to chromosome 21 demonstrated three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The prevalence of this type of chromosomal anomaly is unknown since low level mosaicisms are easily missed. The unusual unbalanced translocation mosaicism detected in this study is uncommon and has not been reported yet [Cohen et al, 1983; Aurias and Dutrillaux, 1986; Farrell, 1991; Petković et al, 1992; Pettenati et al, 1993; Kotzot and Schinzel, 2000]. There are at least two different modes of origin.…”
Section: Discussionsupporting
confidence: 48%
“…The prevalence of this type of chromosomal anomaly is unknown since low level mosaicisms are easily missed. The unusual unbalanced translocation mosaicism detected in this study is uncommon and has not been reported yet [Cohen et al, 1983; Aurias and Dutrillaux, 1986; Farrell, 1991; Petković et al, 1992; Pettenati et al, 1993; Kotzot and Schinzel, 2000]. There are at least two different modes of origin.…”
Section: Discussionsupporting
confidence: 48%
“…In mosaic carriers of Rob/iso carriers detected postnatally (Table III), there is an expected prevalence of rearrangement of chromosome 21 because of the increased survival of individuals with trisomy 21 compared to carriers of trisomy for 13–15 and 22. Although some structural aberrations may have meiotic origin [Kotzot and Schinzel, 2000], formation of mosaicism requires postzygotic events. In this group (Rob/iso carriers) there is a female prevalence (seven males and 12 females), but the difference from the expected sex ratio of 1.06 in the newborn population does not reach statistical significance ( P = 0.2163).…”
Section: Resultsmentioning
confidence: 99%
“…Possibly because of this assumption, the origin of the rearrangement has only been investigated in seven reports and in none do the two cell lines carry different aberrant chromosomes. [19][20][21][22][23][24][25] In three reports a meiotic error occurred first, followed by either a loss or a rearrangement of the trisomic chromosome. 19 22 24 The finding in this patient reinforces the idea that many chromosomal rearrangements occurring in mosaic people may have their origin during meiosis.…”
Section: Discussionmentioning
confidence: 99%